2022
DOI: 10.1097/01.asw.0000818580.47852.68
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Skin Structure: Pressure Injury Staging Challenges

Abstract: To review neonatal pressure injuries (PIs), including clinical features and challenges in evaluation and staging related to the unique anatomic features of preterm neonatal skin as well as the common sites and mechanisms of injury.TARGET AUDIENCE: This continuing education activity is intended for physicians, physician assistants, nurse practitioners, and nurses with an interest in skin and wound care. LEARNING OBJECTIVES/OUTCOMES: After participating in this educational activity, the participant will: 1. Reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Risk factors for HAPI development include exposure to various diagnostic and therapeutic medical devices, inactivity or immobility, friction and shear, hypoxia and poor skin perfusion, fluid retention, and nutrition deficiencies; critically ill neonates may be exposed to all of these factors 23,24 . Visscher and Taylor 25 found a 6.4% rate of medical device-related PIs in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for HAPI development include exposure to various diagnostic and therapeutic medical devices, inactivity or immobility, friction and shear, hypoxia and poor skin perfusion, fluid retention, and nutrition deficiencies; critically ill neonates may be exposed to all of these factors 23,24 . Visscher and Taylor 25 found a 6.4% rate of medical device-related PIs in neonates.…”
Section: Discussionmentioning
confidence: 99%
“…More often these methods are used in the case of stage 2 diagnosis of bedsores [27]. These therapy methods include ozone, oxygenation, exposure to electricity, magnetic therapy, and the method of photodynamics [28]. A combination of phonophoresis and antiseptics, the effect of ultraviolet light on the areas adjacent to the erythema, and a combination of electrophoresis and antimicrobial drugs are also used.…”
Section: Therapy Methodsmentioning
confidence: 99%
“…4,8,9 Because preterm infants' skin is thin, permeable, and sensitive, their skin integrity is easily disrupted by shear. 8,10,11 Underdevelopment of the nasal tissue further increases the risk of developing medical device-related pressure injuries (MDRPIs) even with short-term NIV. 9,[11][12][13][14][15] It has been reported that 20% to 60% of nasal pressure injuries (PIs) in preterm infants treated in neonatal ICUs (NICUs) are a result of shear from medical devices and equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Nasal injury is the most common preventable complication of NIV 4,8,9 . Because preterm infants’ skin is thin, permeable, and sensitive, their skin integrity is easily disrupted by shear 8,10,11 . Underdevelopment of the nasal tissue further increases the risk of developing medical device-related pressure injuries (MDRPIs) even with short-term NIV 9,11–15 .…”
Section: Introductionmentioning
confidence: 99%